Jewish and Christian doctrines : the classics compared - Neusner, Jacob, 1932-2016 (Routledge, 2000)
Jewish and Christian Doctrines presents a concise and lucid introduction to the foundations of Judaism and Christianity. The authors explore key documents ofJudaism and Christianity to elucidate and illuminate the doctrinal issues which the documents raise and to examine the similarities and differences between the two faiths.